2023
DOI: 10.1002/hsr2.1155
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and pericardial fat volume as predictors of coronary atherosclerosis burden in postmenopausal women: A retrospective, single center study

Abstract: Background and Aims: Little is known about the clinical relevance of pericardial fat volume (PFV), compared to other conventional cardiovascular risk factors, as predictors of coronary atherosclerosis severity among postmenopausal women. Our main aim was to assess the association of PFV and cardiovascular risk factors with coronary atherosclerosis burden, including occlusive coronary artery disease (CAD) (luminal stenosis >50%), coronary artery calcium score (CAC) >100, and plaque types in postmenopausal women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Akin et al (21) indicated the coronary plaque burden was positively correlated with non-HDL-C and TG/ HDL-C ratio. Moreover, Nafakhi et al (22) demonstrated that pericardial fat volume independently associated with coronary atherosclerosis burden.…”
Section: Risk Factors Related To Higher Coronary Plaque Burdenmentioning
confidence: 99%
“…Akin et al (21) indicated the coronary plaque burden was positively correlated with non-HDL-C and TG/ HDL-C ratio. Moreover, Nafakhi et al (22) demonstrated that pericardial fat volume independently associated with coronary atherosclerosis burden.…”
Section: Risk Factors Related To Higher Coronary Plaque Burdenmentioning
confidence: 99%